Rehabilitation and plasticity following stroke: Insights from rodent models. (17th December 2015) - Caleo, M.
Highlights: Considerable map plasticity occurs spontaneously after an ischemic injury to the motor cortex. Physical rehabilitation impacts on spontaneous neuroplasticity and triggers restoration of function. It is critical to distinguish "true" recovery (i.e. re-establishment of original movement patterns) from compensation. Motor recovery can be boosted by a combination of rehabilitation and plasticizing drugs. Abstract: Ischemic injuries within the motor cortex result in functional deficits that may profoundly impact activities of daily living in patients. Current rehabilitation protocols achieve only limited recovery of motor abilities. The brain reorganizes spontaneously after injury, and it is believed that appropriately boosting these neuroplastic processes may restore function via recruitment of spared areas and pathways. Here I review studies on circuit reorganization, neuronal and glial plasticity and axonal sprouting following ischemic damage to the forelimb motor cortex, with a particular focus on rodent models. I discuss evidence pointing to compensatory take-over of lost functions by adjacent peri-lesional areas and the role of the contralesional hemisphere in recovery. One key issue is the need to distinguish "true" recovery (i.e. re-establishment of original movement patterns) from compensation in the assessment of post-stroke functional gains. I also consider the effects of physical rehabilitation, including robot-assisted therapy, and the potential mechanisms by which motor training induces recovery. Finally, I describe experimental approaches in which training is coupled with delivery of plasticizing drugs that render the remaining, undamaged pathways more sensitive to experience-dependent modifications. These combinatorial strategies hold promise for the definition of more effective rehabilitation paradigms that can be translated into clinical practice.